Efektivitas Pengendalian Serangan Penggerek Buah Kakao (Conopomorpha cramerella Snellen) dengan Metode Kondomisasi - Tata Sadori; Zahlul Ikhsan; Yaherwandi Yaherwandi (Universitas Teuku Umar, 2023)
Cocoa pod borer (CPB) is one of the important pests of cacao crops in Indonesia. The percentage of plants attacked by CPB pests at Dharmasraya Regency in 2019 reached 59.93%. Therefore, it is necessary to have appropriate control measures in order to reduce the percentage of plants attacked by CPB pests. One of the controls that are considered capable to controlling CPB pests is the condomization method. The objectives of this research wereto study the effectiveness of cacao pods condomization against C. cramerella attack, and to determine the appropriate cacao pods size for condomization in controlling C. cramerella. The researchwas designed by a Completely Randomized Design (CRD) consisted of 3 treatments and 5 replications, each replication consisted of 2 samples. The treatments used were condomization of cacao pods sized 5-8 cm and 9-12 cm with plastic sized30 cm x 20 cm x 0.5 mm, and the controls. The data were analyzed ofvariance and Duncan's New Multiple Range Test (DNMRT) at 5% level significantly. The results showed that the cacao pods sized5-8 cm that were condomed could reduce the percentage of pod attacked by CPB pests from 89.96% to 40.00% and the percentage of cocoa beans damage from 35.45% to 2.46%. The average of cocoa beans dry weight in this results showed a not too significant difference, ranging from 31.6 g - 47.7 g. CPB pest control using the condomization method on cacao pods is quite effective in controlling CPB pests. The best size for cacao pods to be condomed is 5-8 cm.Keywords: cacao, condomization, Cocoa Pod Borer, pods size 5-8 cm, and 9-12 cm